Provisioning health care infrastructure in communities: Empirical evidences from West Bengal, India. (June 2016) - Jana, Arnab; Harata, Noboru
Abstract: We developed a framework to reinvigorate communities in terms of public health care infrastructure provisioning for outpatient needs within the neighborhoods. The health care seeking episode is often influenced by the physical and health care infrastructure availability within the neighborhood, need of the health care seeker as well as personal, household, occupational, and latent perception of the users. This empirical study has been developed for two different groups in West Bengal India, firstly based on location and secondly based on the choice of the health care seeker. In case of resident based approach, we focused on the revisit decision of the rural inhabitants who sometime tend to travel to the regional facilities in urban areas. Facility based approach analyzed the people who were at the regional facilities for health care services. We devised scenarios ascertaining improvisation in service delivery, emergency facility and mobility ease at local public facilities might reduce regional tours and instigate higher utilization of the neighborhood health care facility. We develop integrated choice and latent variable models to incorporate latent perception in choice of scenario for instigating revisit decision. Results showed choice of development scenarios have association with the household structure, social network, locational and infrastructural impedance. This framework lead to two distinct outcomes: (1) method to identify programs, those are essential to by initiate_revisit_to the health care facility (2) perception based assessment of the current mobility and health care infrastructure of the region, which could be instrumental in developing the overall health care infrastructural planning policy as a whole. Highlights: Formulating health care infrastructure development strategies based on people's heterogeneous needs and aspirations. Homogeneity of access to basic services, lifestyle and occupation patterns were found critical for resident-based approach. Homogeneity of the choice of availing health care service at the regional facilities is important for facility-based approach. Identification of scenarios that are essential to initiate 'revisit' to the neighborhood health care facility. Perception based assessment of the current mobility and health care infrastructure of the region.